2021
DOI: 10.1007/s00247-021-05055-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary imaging in coronavirus disease 2019 (COVID-19): a series of 140 Latin American children

Abstract: Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which resulted in the worldwide coronavirus disease 2019 (COVID-19) pandemic of 2020, has particularly affected Latin America. Objective The purpose of the study was to analyze the imaging findings of pulmonary COVID-19 in a large pediatric series. Materials and methods Children with SARS-CoV-2 infection confirmed by either quantitative reverse transcription-polymera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies that have evaluated radiological variables differ somehow. Investigations carried out in Latin America and Spain found that peribronchial thickening, ground-glass opacities, consolidation, and vascular thickening were frequent ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have evaluated radiological variables differ somehow. Investigations carried out in Latin America and Spain found that peribronchial thickening, ground-glass opacities, consolidation, and vascular thickening were frequent ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Viral sepsis caused by SARS-CoV-2 infection is a well-documented condition in adults, and the patients usually experience pulmonary, renal, hepatic, hematologic, and cardiac involvement, often with positive RT-PCR from respiratory swabs (21). Moreover, a recent study performed on Latin American children proved that in terms of lung impairment, ground-glass opacities and consolidations caused by this virus are commonly associated to severe forms requiring intensive care admission, and even death (22). Similarly, bacterial sepsis displays an increased risk for multiple organ failure in children (23).…”
Section: Discussionmentioning
confidence: 99%
“…(18,(31)(32)(33)(34) Slight to moderate inter-rater agreement regarding CT findings has also been reported in children. (35) However, This study has some limitations, such as retrospective design, small sample size and inclusion of only 2 independent raters. Further multi-center prospective studies with larger samples and a larger number of raters are warranted to confirm our findings.…”
Section: ❚ Resultsmentioning
confidence: 95%